Capitularies in the Ottonian realm. - Patzold, Steffen (Early Medieval Europe, 2019)
This essay is a study of the transmission and later use of Carolingian capitularies. Issued in the ninth century, in a number of cases these documents are known to us only through copies made in the tenth century, in the Ottonian empire. The goal of the study is to prompt a rethinking of the contrast often drawn between the text‐based legal culture of the Carolingian empire and the supposedly oral and ritual culture of Ottonian rule. A survey of seventeen capitulary manuscripts is offered, followed by two case studies. The first concerns a tenth‐century Metz manuscript; the second centres around a Mainz book. These appeal to the Carolingian past in order to shape legal claims in the present: as assemblages of legal texts, they bear important witness to the context of their production.